An Overview of Tourism Sector in the Post-Covid-19 Period and beyond among East Africa Countries - Njue, Michael; Nyamogosa, Henry; Lopar, Samuel; Amata, Mwalo (International Journal of Research in Tourism and Hospitality (IJRTH), 2025)
The paper gives an overview of the tourism sector in the post Covid-19 period among East African Countries which forms the East African Community (EAC) an intergovernmental organization comprised of 7 nations in East Africa. The article introduces the EAC region and tourism industry, its current status, and significance. The study’s findings are based on desktop research methodology that relied on published reports, studies, and statistics. Further, the paper summarizes the tourism industry of member states before, during, and the period after the Covid-19 pandemic in the region. The article provides statistical evidence on the Post Covid-19 tourism numbers reflecting growth and recovery from the Covid-19 pandemic. Further, the study provides the pathways and opportunities for states and region for the recovery, growth, and development beyond the pandemic. In conclusion, the statistical evidence provided finds that most of East African countries are at above 50 percent recovery level. The study recommends a more organized open data collection regarding the tourism industry in the east African countries for a longer period as a necessity. The growing body of research on the tourism industry necessitates the emphasis on this rigorous data collection and documentation.